This site is supported by donations to The OEIS Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A118344 Pendular Catalan triangle, read by rows, where row n is formed from row n-1 by the recurrence: if n > 2k, T(n,k) = T(n,n-k) + T(n-1,k), else T(n,k) = T(n,n-1-k) - T(n-1,k) - T(n-1,k+1), for n>=k>=0, with T(n,0)=1 and T(n,n)=0^n. 1
 1, 1, 0, 1, 1, 0, 1, 2, 1, 0, 1, 3, 2, 1, 0, 1, 4, 5, 3, 1, 0, 1, 5, 9, 5, 4, 1, 0, 1, 6, 14, 14, 9, 5, 1, 0, 1, 7, 20, 28, 14, 14, 6, 1, 0, 1, 8, 27, 48, 42, 28, 20, 7, 1, 0, 1, 9, 35, 75, 90, 42, 48, 27, 8, 1, 0, 1, 10, 44, 110, 165, 132, 90, 75, 35, 9, 1, 0, 1, 11, 54, 154, 275, 297, 132 (list; table; graph; refs; listen; history; text; internal format)
 OFFSET 0,8 COMMENTS See A118340 for definition of pendular triangles and pendular sums. LINKS FORMULA T(2*n+m,n) = [A000108^(m+1)](n), i.e., the m-th lower semi-diagonal forms the self-convolution (m+1)-power of A000108. EXAMPLE Row 6 equals the pendular sums of row 5: [1, 4, 5, 3, 1, 0], where the sums proceed as follows: [1,__,__,__,__,__]: T(6,0) = T(5,0) = 1; [1,__,__,__,__, 1]: T(6,5) = T(6,0) - T(5,5) = 1 - 0 = 1; [1, 5,__,__,__, 1]: T(6,1) = T(6,5) + T(5,1) = 1 + 4 = 5; [1, 5,__,__, 4, 1]: T(6,4) = T(6,1) - T(5,4) - T(5,5) = 5-1-0 = 4; [1, 5, 9,__, 4, 1]: T(6,2) = T(6,4) + T(5,2) = 4 + 5 = 9; [1, 5, 9, 5, 4, 1]: T(6,3) = T(6,2) - T(5,3) - T(5,4) = 9-3-1 = 5; [1, 5, 9, 5, 4, 1, 0] finally, append a zero to obtain row 6. Triangle begins: 1; 1, 0; 1, 1, 0; 1, 2, 1, 0; 1, 3, 2, 1, 0; 1, 4, 5, 3, 1, 0; 1, 5, 9, 5, 4, 1, 0; 1, 6, 14, 14, 9, 5, 1, 0; 1, 7, 20, 28, 14, 14, 6, 1, 0; 1, 8, 27, 48, 42, 28, 20, 7, 1, 0; 1, 9, 35, 75, 90, 42, 48, 27, 8, 1, 0; 1, 10, 44, 110, 165, 132, 90, 75, 35, 9, 1, 0; 1, 11, 54, 154, 275, 297, 132, 165, 110, 44, 10, 1, 0; ... Central terms are Catalan numbers T(2*n,n) = A000108(n); semi-diagonals form successive self-convolutions of the central terms: T(2*n+1,n) = [A000108^2](n), T(2*n+2,n) = [A000108^3](n). PROG (PARI) {T(n, k)=if(n2*k, T(n, n-k)+T(n-1, k), T(n, n-1-k)-T(n-1, k)-if(n-1>k, T(n-1, k+1)) ))))} CROSSREFS Cf. A000108, A118340. Cf. A033184 [From Philippe DELEHAM, Nov 13 2009] Sequence in context: A100995 A136566 A048983 * A119270 A175804 A195017 Adjacent sequences:  A118341 A118342 A118343 * A118345 A118346 A118347 KEYWORD nonn,tabl AUTHOR Paul D. Hanna, Apr 26 2006 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Transforms | Puzzles | Hot | Classics
Recent Additions | More pages | Superseeker | Maintained by The OEIS Foundation Inc.

Content is available under The OEIS End-User License Agreement .